Mucoidy, a general mechanism for maintaining lytic phage in populations of bacteria. Issue 10 (26th August 2020) - Chaudhry, Waqas; Lee, Esther; Worthy, Andrew; Weiss, Zoe; Grabowicz, Marcin; Vega, Nicole; Levin, Bruce
ABSTRACT: We present evidence that phage resistance resulting from overproduction of exopolysaccharides, mucoidy, provides a general answer to the longstanding question of how lytic viruses are maintained in populations dominated by bacteria upon which they cannot replicate. In serial transfer culture, populations of mucoid Escherichia coli MG1655 that are resistant to lytic phages with different receptors, and thereby requiring independent mutations for surface resistance, are capable of maintaining these phages with little effect on their total density. Based on the results of our analysis of a mathematical model, we postulate that the maintenance of phage in populations dominated by mucoid cells can be attributed primarily to high rates of transition from the resistant mucoid states to susceptible non-mucoid states. Our tests with both population dynamic and single cell experiments as well as genomic analysis are consistent with this hypothesis. We discuss reasons for the generalized resistance of these mucoid E. coli, and the genetic and molecular mechanisms responsible for the high rate of transition from mucoid to sensitive states responsible for the maintenance of lytic phage in mucoid populations of E. coli . Abstract : The overproduction exopolysaccharides, mucody, is a general mechanism for the maintenance of lytic phage in resistant populations of bacteria.